Cardiac CaMKII activation promotes rapid translocation to its extra-dyadic targets. (December 2018) - Wood, Brent M.; Simon, Mitchell; Galice, Samuel; Alim, Chidera C.; Ferrero, Maura; Pinna, Natalie N.; Bers, Donald M.; Bossuyt, Julie
Abstract: Calcium-calmodulin dependent protein kinase IIδ (CaMKIIδ) is an important regulator of cardiac electrophysiology, calcium (Ca) balance, contraction, transcription, arrhythmias and progression to heart failure. CaMKII is readily activated at mouths of dyadic cleft Ca channels, but because of its low Ca-calmodulin affinity and presumed immobility it is less clear how CaMKII gets activated near other known, extra-dyad targets. CaMKII is typically considered to be anchored in cardiomyocytes, but while untested, mobility of active CaMKII could provide a mechanism for broader target phosphorylation in cardiomyocytes. We therefore tested CaMKII mobility and how this is affected by kinase activation in adult rabbit cardiomyocytes. We measured translocation of both endogenous and fluorescence-tagged CaMKII using immunocytochemistry, fluorescence recovery after photobleach (FRAP) and photoactivation of fluorescence. In contrast to the prevailing view that CaMKII is anchored near its myocyte targets, we found CaMKII to be highly mobile in resting myocytes, which was slowed by Ca chelation and accelerated by pacing. At low [Ca], CaMKII was concentrated at Z -lines near the dyad but spread throughout the sarcomere upon pacing. Nuclear exchange of CaMKII was also enhanced upon pacing- and heart failure-induced chronic activation. This mobilization of active CaMKII and its intrinsic memory may allow CaMKII to be activated in high [Ca] regions and then move towards more distant myocyte target sites. Highlights: Cardiac CaMKII is predominantly mobile. CaMKII mobility varies with calcium/kinase activation. Active CaMKII moves from the dyadic cleft towards cytosolic targets including PLB. Heart failure promotes movement of CaMKII out of the nucleus.